2008
DOI: 10.1029/2007ja012844
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal evening vertical plasma drift and effects on ESF and EIA over Brazil‐South Atlantic sector during the 30 October 2003 superstorm

Abstract: [1] Equatorial F region vertical plasma drifts, spread F and anomaly responses, in the south American longitude sector during the superstorm of 30 October 2003, are analyzed using data from an array of instruments consisting of Digisondes, a VHF radar, GPS TEC and scintillation receivers in Brazil, and a Digisonde and a magnetometer in Jicamarca, Peru. Prompt penetrating eastward electric field of abnormally large intensity drove the F layer plasma up at a velocity $1200 ms À1 during post dusk hours in the eas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
91
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(95 citation statements)
references
References 39 publications
3
91
1
Order By: Relevance
“…In such cases, strong scintillations occur near the boundaries of the depletion region, and only weak scintillations occur in the low-density region. Abdu et al [44] have analyzed the characteristics of ionospheric scintillations in the Brazilian sector during the magnetic storm on 30 October 2003. Some previous studies [33][34][35][36] found that enhanced magnetic activity suppressed the occurrence of plasma bubbles in the evening sector.…”
Section: Discussionmentioning
confidence: 99%
“…In such cases, strong scintillations occur near the boundaries of the depletion region, and only weak scintillations occur in the low-density region. Abdu et al [44] have analyzed the characteristics of ionospheric scintillations in the Brazilian sector during the magnetic storm on 30 October 2003. Some previous studies [33][34][35][36] found that enhanced magnetic activity suppressed the occurrence of plasma bubbles in the evening sector.…”
Section: Discussionmentioning
confidence: 99%
“…The third CalVal campaign began in March 2010 and will continue to the end of 2011. Easy access via GIRO to the globally distributed measurements of the ionospheric plasma has also inspired a number of studies of the ionospheric response to space weather events (e.g., Abdu et al, 2008;Lei et al, 2008;Paznukhov et al, 2009;Zong et al, 2010;Stanislawska et al, 2010).…”
Section: Giro Research Projectsmentioning
confidence: 99%
“…Electric field disturbances have been suggested as the most important contributor mechanism to explain the initial F2-region response to geomagnetic storms during daytime (see, for example, Abdu, 1997;Abdu et al, , 2007Abdu et al, , 2008Batista et al, 2012 and references therein). This is possibly because the structure and dynamics of the quiet time equatorial ionosphere is determined by an eastward electric field in conjunction with the geomagnetic field.…”
Section: Introductionmentioning
confidence: 99%